Electric leakage response thin film material and preparation method and application thereof

By using a leakage response thin film material with a single composite layer structure in power equipment, the problems of high response threshold, slow speed and poor memory effect of traditional electrochromic devices in weak leakage current detection are solved, and rapid response and long-term memory of microampere leakage current are achieved, simplifying the preparation process and reducing costs.

CN120757815APending Publication Date: 2025-10-10YUNNAN POWER GRID CO LTD ELECTRIC POWER RES INST +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510801628.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-16
Publication Date
2025-10-10

AI Technical Summary

Technical Problem

Existing electrochromic devices have a high response threshold, slow response speed, poor memory effect and complex structure in detecting weak leakage currents in power equipment, making it difficult to meet the needs of long-term, intuitive and low-cost monitoring of tiny leakage currents in power equipment.

Method used

A single composite layer structure is used to evenly disperse tungsten trioxide particles and lithium ion sources in a cross-linked polymer matrix, shortening the ion migration path to the nanoscale. The polymer chain segment entanglement effect and ion steric hindrance are utilized to achieve rapid response and long-term memory.

Benefits of technology

It achieves sensitive response to the early microampere-level leakage current of power equipment, color change speed in seconds, and color memory effect of several weeks, reducing production costs and improving the applicability of materials in high-voltage environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120757815A_ABST
    Figure CN120757815A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrochromic materials, and particularly relates to an electric leakage response film material and a preparation method and application thereof. The invention relates to an electric leakage response film material, which is a single composite layer and comprises a cross-linked polymer matrix formed by polyethylene glycol diglycidyl ether and polyether amine through an epoxy-amine reaction; the tungsten trioxide particles are dispersed in the cross-linked polymer matrix; and a source of lithium ions dispersed in the cross-linked polymer matrix.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of electrochromic materials, and particularly relates to a leakage current response film material and a preparation method and application thereof. BACKGROUND

[0002] The safe and stable operation of a power system is the cornerstone of the normal operation of modern society, and electrical equipment, especially high-voltage power equipment, may gradually deteriorate in insulation performance during long-term operation due to environmental factors, material aging, installation defects or overloading, etc., resulting in the generation of a small leakage current. If these small leakage currents are not discovered and handled in time, they may develop into partial discharge, insulation breakdown or even cause equipment damage, fires and large-scale power outage accidents, which pose a serious threat to the safety and economic benefits of the power system. Therefore, developing an efficient, sensitive and reliable leakage current detection technology, especially a monitoring method for early and weak leakage signals, is of great significance to ensuring the safety of power equipment and preventing accidents.

[0003] At present, traditional leakage current detection methods mainly include the current transformer method, the ammeter method and the current sensor method based on the Hall effect principle. The current transformer method performs well under strong current or at a specific frequency, but has poor response to low-frequency slowly varying leakage current or direct current leakage current, and has the problem of core saturation. The ammeter method usually needs to be connected in series with the circuit, which has the risk of intrusive measurement, and it is difficult to balance between high sensitivity and wide range. Although the current sensor has high precision, it is often expensive, some sensors have temperature drift problems, and usually needs to be connected with an external power supply and signal processing circuit, which is complex to deploy and difficult to achieve economic and convenient monitoring of a large number of dispersed equipment. In addition, these traditional methods rely on the collection and transmission of electrical signals, which requires the operation and maintenance personnel to use professional instruments for interpretation, and cannot provide intuitive and real-time on-site fault indication.

[0004] In view of the limitations of traditional leakage detection methods, electrochromic technology provides a promising approach for visualizing leakage current due to its reversible color change under an applied electric field. Existing electrochromic devices typically have a multilayer stack structure of "transparent conductive layer / electrochromic layer / electrolyte layer / ionic storage layer / transparent conductive layer". This structure has been applied in low-voltage electronic devices such as smart windows, but direct application in power equipment leakage current detection faces many challenges. For example, its color change threshold current is usually in the order of milliamperes, making it difficult to respond to early microampere-level weak leakage current in power equipment; the migration path of ions between multiple interfaces is long, resulting in a long color development response time that cannot meet the demand for real-time monitoring; after power failure, the colored state usually fades quickly due to the reverse diffusion of ions in the electrolyte, lacking long-term memory effect, so that the inspection personnel may miss the short-term leakage event; at the same time, the multilayer structure also has deficiencies in adhesion on the surface of complex power equipment, high-voltage resistance, manufacturing cost and process complexity, etc. Therefore, the existing technical solutions cannot directly and effectively meet the needs of long-term, intuitive and low-cost monitoring of small leakage current in power equipment, and there is an urgent need for a new leakage detection material that can respond quickly under weak current drive and maintain a colored state for a long time, with a simple structure and easy application. SUMMARY

[0005] The purpose of the present application is to solve the above technical problems, and provide a leakage response film material and its preparation method and application.

[0006] The core idea of the present application is derived from the deep understanding of the limitations of existing electric power equipment leakage current detection technology, especially the high response threshold, slow response speed, poor memory effect and complex structure of traditional electrochromic devices when applied to weak leakage current (μA level) monitoring. The inventors realized that the traditional multi-layer stacked electrochromic structure is the root cause of the above problems, because the migration of ions between different material layers not only has a long path and high resistance, but also the matching and stability of the interlayer interface are difficult to guarantee, and the complex structure also limits its application potential and cost control in high voltage and complex environments. Therefore, to fundamentally break through these bottlenecks, it is necessary to overturn the traditional multi-layer device design paradigm and seek an innovative path that can highly integrate electrochromic, ion storage and ion conduction functions in a single material system. Based on this, the inventors conceived that if a single composite layer material could be constructed, in which the electrochromic active component (such as tungsten trioxide nanoparticles) and the ion source (such as lithium salt) could be uniformly dispersed and stably exist in a specially designed polymer matrix, then the migration path of ions under the driving of leakage current would be shortened from microns to nanometers, which not only greatly reduces the driving current threshold required for color change to the microampere level, significantly improves the response speed to the second level, but also effectively inhibits the reverse diffusion of ions after power-off through the dynamic entanglement effect of polymer segments and the steric hindrance effect with specific ions (such as large volume anions), thereby realizing a memory effect of several weeks. Further, this single composite layer structure essentially simplifies the material preparation process, reduces production costs, and improves the overall electrical strength of the film by selecting and designing a polymer matrix (such as a cross-linked epoxy-amine system with high insulation strength and excellent flexibility), which can be directly applied to the surface of high-voltage electrical equipment to realize in-situ and direct leakage state indication. In summary, the present application fundamentally changes from a multi-layer structure to a single integrated composite material, cleverly utilizes the nanoscale effect and the unique properties of polymer materials, aiming to realize a new type of leakage response film material with high sensitivity to microampere level leakage current, fast response, long memory, good electrical performance, and simple structure, easy to deploy.

[0007] In a first aspect, a leakage response film material adopts the following technical solution:

[0008] A leakage response film material, the leakage response film material is a single composite layer, comprising:

[0009] A cross-linked polymer matrix formed by epoxy-amine reaction of polyethylene glycol diglycidyl ether and polyether amine;

[0010] Tungsten trioxide particles dispersed in the cross-linked polymer matrix; and

[0011] A lithium ion source dispersed in the cross-linked polymer matrix.

[0012] Further, the molar ratio of the polyethylene glycol diglycidyl ether to the polyether amine is 1:(0.7-0.9).

[0013] Further, the electric leakage responsive thin film material comprises:

[0014] the tungsten trioxide particles in a mass percentage of 1%-50%;

[0015] the lithium ion source in a mass percentage of 1%-25%; and

[0016] the cross-linked polymer matrix in a mass percentage of 99%-50%.

[0017] Further, the tungsten trioxide particles have a particle size of 50 nm-200 nm, a specific surface area ≥ 30 m 2 / g, and the surface of the tungsten trioxide particles is modified by 3-aminopropyl triethoxysilane, and the amine group density on the surface after modification is ≥ 1.2 / nm 2 .

[0018] Further, the lithium ion source is at least one selected from lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium triflate, and lithium bis(fluorosulfonyl)imide.

[0019] Further, the electric leakage responsive thin film material has a thickness of 50 μm-200 μm.

[0020] Further, the cross-linked polymer matrix has an ionic conductivity greater than 1×10 -4 S / cm, and the cross-linked polymer matrix has a volume resistivity greater than 1×10 14 Ω·cm.

[0021] In a second aspect, a preparation method of an electric leakage responsive thin film material is provided, which adopts the following technical scheme:

[0022] A preparation method of an electric leakage responsive thin film material comprises the following steps:

[0023] S1, mixing polyethylene glycol diglycidyl ether and polyether amine and performing prepolymerization to form a low-viscosity prepolymer;

[0024] S2, adding tungsten trioxide particles and a lithium ion source to the low-viscosity prepolymer and performing dispersion treatment to obtain a uniform slurry;

[0025] S3, forming a film of the uniform slurry on a substrate and performing solidification treatment to form the cross-linked polymer matrix, thereby obtaining the electric leakage responsive thin film material.

[0026] Further, the pre-polymerization in step S1 is performed at 50-70 DEG C for 20-45 min; the dispersion treatment in step S2 comprises high-speed shearing emulsification and ultrasonic dispersion, and the dispersion time is 0.5-1.5 h; the film formation in step S3 is performed by slit coating, and the curing treatment is performed at 70-90 DEG C for 1.5-3.0 h.

[0027] In a third aspect, an application of the electric leakage responsive thin film material adopts the technical scheme as follows.

[0028] An application of the electric leakage responsive thin film material in electric leakage current detection of electric power equipment, the electric leakage responsive thin film material is made into a visual indicator device, which is directly attached to the surface of the electric power equipment, and indicates the electric leakage state through color change driven by the electric leakage current.

[0029] The electric leakage responsive thin film material has the following advantages.

[0030] The electric leakage responsive thin film material is a single composite layer structure, which highly integrates and uniformly disperses the electrochromic active component (tungsten trioxide particles) and the ion source (lithium ion source) in the cross-linked polymer matrix, so that the migration path of the ion under the driving of the electric leakage current is significantly shortened from the micron level of the traditional multilayer structure to the nanometer level, and the color change response current threshold is greatly reduced, so that the material can sensitively respond to the early microampere level of the weak electric leakage current of the electric power equipment, thereby making up for the defect that the traditional device is not sensitive to the small electric leakage; the extremely short ion migration path also greatly improves the color development response speed of the material, and can realize the color change in seconds, thereby meeting the demand for real-time monitoring of the electric leakage event; secondly, the electric leakage responsive thin film material, especially the polymer matrix, can effectively anchor the ion state after color change, significantly inhibit the reverse diffusion of the ion in the color fading process after power failure, thereby giving the material a color memory effect of several weeks, ensuring that even intermittent or short-term electric leakage events can be effectively recorded and found by the inspection personnel in time. In addition, the single composite layer structure simplifies the preparation process, reduces the cost, and improves the applicability and reliability of the material on the surface of the high-voltage and complex electric power equipment, thereby providing an intuitive, convenient and economical and efficient electric leakage current visual monitoring method for the electric power equipment. BRIEF DESCRIPTION OF DRAWINGS

[0031] Figure 1 The F element distribution map of the surface of the electric leakage responsive thin film material prepared in the embodiment of the present application;

[0032] Figure 2 The S element distribution map of the surface of the electric leakage responsive thin film material prepared in the embodiment of the present application;

[0033] Figure 3 W element distribution map of the surface of the electric leakage response thin film material prepared in the embodiment of the present application;

[0034] Figure 4 Color change photo of the electric leakage response thin film material prepared in the embodiment of the present application under the action of 0.1 μA current for 3 s;

[0035] Figure 5 Color path schematic diagram of the electric leakage response thin film material prepared in the embodiment of the present application on the CIE chromaticity diagram;

[0036] Figure 6 Color state photo of the electric leakage response thin film material prepared in the embodiment of the present application in the color memory effect test, 15 days after the current is removed;

[0037] Figure 7 Weibull distribution map of the breakdown field strength of the electric leakage response thin film material containing tungsten trioxide particles with different mass concentrations. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solutions and advantages of the present application clearer, the present application will be described in further detail below with reference to the drawings, and the described embodiments should not be regarded as limiting the present application. All other embodiments obtained by those skilled in the art without making creative efforts belong to the scope of protection of the present application.

[0039] In the following description, "some embodiments" are related to a subset of all possible embodiments, but it can be understood that "some embodiments" can be the same subset or different subsets of all possible embodiments, and can be combined with each other without conflict. Unless otherwise defined, all technical and scientific terms used in the embodiments of the present application have the same meaning as understood by those skilled in the art to which the embodiments of the present application belong. The terms used in the embodiments of the present application are only for the purpose of describing the embodiments of the present application, and are not intended to limit the present application.

[0040] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of the serial numbers does not mean the order of execution, and some or all steps can be executed in parallel or in sequence, and the execution order of each process should be determined according to its function and inherent logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0041] The terms used in the embodiments of the present application are only for the purpose of describing the specific embodiments, and are not intended to limit the present application. The singular forms "a" and "the" used in the embodiments of the present application and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.

[0042] It should be understood by those skilled in the art that numerical ranges in the embodiments of the present application are to be understood to include every intermediate value and any other intervening range between the upper and lower limits of that range. Every intermediate value and other intervening range between any stated value and stated range, and between any stated value or intervening value in the stated range, is included herein. The upper and lower limits of these smaller ranges can independently be included or excluded in the ranges.

[0043] Unless defined otherwise, all technical / scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. Although any methods and materials similar or equivalent to those described herein can be used in the practice of the present application, the preferred methods and materials are described herein. All documents mentioned herein are incorporated by reference to disclose and describe in full the methods and / or materials which are described therein. In the event of conflict between the present application and any incorporated document, the present application controls.

[0044] It should be noted that all raw materials and / or reagents in the embodiments of the present application are either commercially available or prepared according to conventional methods well known to those skilled in the art.

[0045] The present embodiment provides a leakage-responsive thin film material, which is a single composite layer comprising:

[0046] a cross-linked polymer matrix formed from polyethylene glycol diglycidyl ether and polyether amine through epoxy-amine reaction;

[0047] tungsten trioxide particles dispersed in the cross-linked polymer matrix; and

[0048] a lithium ion source dispersed in the cross-linked polymer matrix.

[0049] The present embodiment provides a leakage-responsive thin film material. The core feature of the material is its "single composite layer" structure. In specific implementation, polyethylene glycol diglycidyl ether (PEGDGE) is first selected as the epoxy monomer, and one or more polyether amines (molecular weight in the range of D400-D2000) are selected. PEGDGE and polyether amines are mixed in a molar ratio. Then, nano-sized tungsten trioxide particles are selected as the electrochromic active substance, and a suitable lithium salt (such as lithium bis(trifluoromethanesulfonyl)imide, LiTFSI) is selected as the lithium ion source. The tungsten trioxide particles and the lithium ion source are uniformly dispersed in the mixture of PEGDGE and polyether amines to form a uniform slurry. Subsequently, the slurry is coated on a suitable substrate (such as a PET film), and the epoxy-amine ring-opening polymerization and cross-linking reaction of PEGDGE and polyether amines are initiated by heating or other means to form a three-dimensional network structure of the cross-linked polymer matrix. In this process, the tungsten trioxide particles and the lithium ion source are encapsulated and fixed in the single polymer matrix layer formed, and finally a leakage-responsive thin film material with a single composite layer structure is obtained. The single composite layer integrates the functions of electrochromism, ion conduction and ion storage.

[0050] In some embodiments, the molar ratio of the polyethylene glycol diglycidyl ether to the polyether amine is 1:(0.7-0.9).

[0051] In the implementation of the leakage-responsive thin film material described in the above specific embodiments, in order to obtain the ideal cross-linked network structure, mechanical properties and ion conduction performance, the molar ratio of polyethylene glycol diglycidyl ether (PEGDGE) to polyether amine is controlled. Specifically, a certain amount of PEGDGE can be weighed, and then according to the target molar ratio of 1:(0.7-0.9), the corresponding amount of polyether amine is calculated and weighed. For example, if the molar amount of PEGDGE is 1 mol, the molar amount of polyether amine can be selected between 0.7 mol and 0.9 mol, such as 0.8 mol. By adjusting the molar ratio, the cross-linking density and the flexibility of the polymer chain segment can be adjusted, thereby affecting the mechanical properties of the material, the migration rate of lithium ions in the matrix, and the final electrochromic performance. Selecting a molar ratio within this range helps to maintain a certain chain segment activity while ensuring sufficient cross-linking, which is beneficial to ion migration.

[0052] In some embodiments, the leakage-responsive thin film material comprises:

[0053] The tungsten trioxide particles account for 1%-50% of the mass;

[0054] The lithium ion source accounts for 1%-25% of the mass; and

[0055] The cross-linked polymer matrix accounts for the balance of the mass.

[0056] In the process of preparing the leakage-responsive thin film material described in the above specific embodiments, the content of tungsten trioxide particles and lithium ion source is a key factor affecting the material's color change performance and ionic conductivity. Taking the total mass of the single composite layer thin film material formed finally as 100%, the mass percentage of tungsten trioxide particles can be adjusted to be in the range of 1% to 50%. For example, 10wt% of tungsten trioxide particles can be added. Similarly, the amount of lithium ion source (such as LiTFSI) is also controlled in the range of 1% to 25% of the mass percentage, for example, 20wt% of LiTFSI is selected to be added. In addition to these two components, the remaining mass part is the cross-linked polymer matrix formed by the reaction of PEGDGE and polyetheramine. Through experimental optimization, the appropriate mass percentage can balance the color change depth, response speed, and mechanical stability and processability of the material.

[0057] In some embodiments, the tungsten trioxide particles have a particle size of 50nm-200nm, a specific surface area of ≥30m 2 / g, and the surface of the tungsten trioxide particles is modified with 3-aminopropyltriethoxysilane, and the amine group density on the surface after modification is ≥1.2 / nm 2 .

[0058] To realize the leakage-responsive thin film material described in the above specific embodiments, the physical and chemical properties of the tungsten trioxide particles used are specifically selected and treated. Tungsten trioxide nanoparticles with an average particle size in the range of 50nm to 200nm are selected, for example, tungsten trioxide particles with an average particle size of 100nm. At the same time, these particles are required to have a larger specific surface area, for example, greater than or equal to 30m 2 / g, to provide more reactive sites. Before use, the tungsten trioxide nanoparticles are subjected to surface modification treatment, specifically using 3-aminopropyltriethoxysilane (APTES) as a silane coupling agent. The tungsten trioxide nanoparticles are dispersed in a solvent (such as an ethanol aqueous solution) containing APTES, and the reaction is carried out under certain conditions (such as heating and stirring) to make APTES molecules form stable chemical bonds with the hydroxyl groups on the surface of the tungsten trioxide particles through hydrolysis and condensation. After modification, it is confirmed through appropriate characterization means that the amine group density on the surface of the particles reaches or exceeds 1.2 / nm 2 . This surface modification helps to improve the dispersibility of tungsten trioxide particles in the polymer matrix and may affect the ion exchange and charge transfer at the interface.

[0059] In some embodiments, the lithium ion source is at least one selected from lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium triflate, and lithium bis(fluorosulfonyl)imide.

[0060] In preparing the leakage-responsive thin film material described in the above specific embodiments, the selection of lithium ion source as the key component to provide mobile lithium ions is critical to the ionic conductivity and electrochemical stability of the material. One or more of the following commonly used lithium salts can be selected for use in combination: lithium bistrifluoromethanesulfonylimide, lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium triflate, or lithium bis(fluorosulfonyl)imide. For example, in one specific embodiment, LiTFSI is selected as the lithium ion source because of its good solubility, thermal stability, and electrochemical stability, and its TFSI - The anion has a large volume, which helps to form steric hindrance after power failure, enhancing the memory effect. Other listed lithium salts or mixtures thereof can also be considered for use as needed to regulate the specific performance of the material.

[0061] In some embodiments, the leakage-responsive thin film material has a thickness of 50 μm to 200 μm.

[0062] To obtain a leakage-responsive thin film material with practicality, the thickness of the single composite layer formed finally needs to be controlled within a specific range. In the preparation process, when the slurry containing the components is coated on the substrate, for example, by slot coating or other coating processes, the thickness of the wet film can be controlled by adjusting the coating parameters (such as doctor blade gap, coating speed, etc.), and the final dry film is formed in the subsequent curing process. In one embodiment of the present application, the thickness of the single composite layer is controlled to be between 50 μm and 200 μm, for example, a thin film with a thickness of 100 μm can be prepared. This thickness range can ensure that the material has sufficient mechanical strength and sufficient active substance content to produce a significant color change, and at the same time, it will not be too thick to affect the flexibility and ion migration efficiency.

[0063] In some embodiments, the ionic conductivity of the cross-linked polymer matrix is greater than 1 x 10 -4 S / cm, and the volume resistivity of the cross-linked polymer matrix is greater than 1 x 10 14 Ω·cm.

[0064] To enable the prepared leakage-responsive thin film material to effectively respond to weak leakage current while maintaining good insulation properties, the core cross-linked polymer matrix (formed by the reaction of PEGDGE and polyetheramine and containing a lithium ion source) needs to meet specific electrical performance requirements. By selecting appropriate PEGDGE, polyetheramine species, and their molar ratio, as well as appropriate lithium ion source species and content, the performance of the formed cross-linked polymer matrix can be regulated. In a specific implementation, it should be ensured that the ionic conductivity of the matrix, measured by AC impedance and the like at room temperature, is greater than 1 x 10 -4 S / cm to ensure that lithium ions can effectively migrate under a weak electric field. At the same time, the volume resistivity of the matrix, measured by DC resistance test and the like, is greater than 1 x 1014 Ω·cm, to ensure that the material itself has a high enough insulation strength to avoid breakdown or the generation of an undesirable conductive path in a high-voltage environment, thereby ensuring the accuracy and safety of leakage detection.

[0065] The embodiment provides a preparation method of a leakage-responsive thin film material, comprising the following steps:

[0066] S1, mixing polyethylene glycol diglycidyl ether and polyether amine and performing prepolymerization to form a low-viscosity prepolymer;

[0067] S2, adding tungsten trioxide particles and a lithium ion source to the low-viscosity prepolymer and performing dispersion treatment to obtain a uniform slurry;

[0068] S3, forming a film of the uniform slurry on a substrate and performing solidification treatment to form the crosslinked polymer matrix, i.e., the leakage-responsive thin film material.

[0069] In a specific embodiment, a preparation method of a high-performance leakage-responsive thin film material is provided, comprising the following steps:

[0070] Step S1: formation of a prepolymer. First, polyethylene glycol diglycidyl ether (PEGDGE) and polyether amine are weighed according to the molar ratio. The two are mixed thoroughly in a reaction container. Then, prepolymerization is performed at a certain temperature (for example, 60°C) for a period of time (for example, 30 min). The purpose of this step is to allow PEGDGE and polyether amine to undergo partial ring-opening and chain growth reactions, forming a prepolymer with increased molecular weight but still maintaining a low viscosity, which is helpful for the uniform dispersion of solid particles in the subsequent step.

[0071] Step S2: introduction and dispersion of functional components. After the prepolymer is cooled to an appropriate temperature, surface-modified tungsten trioxide nanoparticles and a selected lithium ion source are added to the low-viscosity prepolymer according to the amount and specifications. Then, high-efficiency dispersion means, such as high-speed shearing stirring combined with ultrasonic dispersion treatment, are used for a period of time (for example, 1 h), to ensure that the tungsten trioxide particles and the lithium ion source are uniformly and stably dispersed in the prepolymer, forming a macroscopically uniform slurry without obvious agglomeration.

[0072] Step S3: film forming and curing. The uniform slurry prepared in step S2 is uniformly coated on the pretreated substrate material (such as PET film) by using a suitable coating method (such as slot coating, doctor blade coating or screen printing) to form a wet film with a desired thickness. Then, the substrate with the wet film is placed in an oven or heated by other heating methods at a certain curing temperature (for example 80℃) for a certain period of time (for example 2h). In this process, the epoxy groups in the prepolymer further crosslink with the amine groups to form a three-dimensional network structure of crosslinked polymer matrix, while the tungsten trioxide particles and lithium ion source are encapsulated therein, and finally a single composite layer of leakage current response thin film material meeting the performance requirements is obtained.

[0073] In some embodiments, the conditions of the prepolymerization in step S1 are carried out at 50-70℃ for 20-45min; the dispersion treatment in step S2 includes high-speed shearing emulsification and ultrasonic dispersion, and the dispersion time is 0.5-1.5h; the film forming in step S3 uses slot coating, and the conditions of the curing treatment are carried out at 70-90℃ for 1.5-3.0h.

[0074] In the implementation of the above specific preparation method, in order to obtain better material performance and process controllability, the process parameters of each step are specifically limited.

[0075] In step S1, after mixing PEGDGE and polyetheramine, the temperature of the prepolymerization is controlled in the range of 50-70℃, for example, 60℃ is selected; the time of the prepolymerization is controlled in the range of 20-45min, for example, 30min is selected.

[0076] In step S2, after adding tungsten trioxide particles and lithium ion source, the dispersion treatment is carried out by combining high-speed shearing emulsification and ultrasonic dispersion, and the total dispersion time is controlled in the range of 0.5-1.5h, for example, 1h is selected to ensure that the components are fully uniform.

[0077] In step S3, the specific method of film forming is selected as slot coating to obtain a uniform coating thickness. The temperature of the subsequent curing treatment is controlled in the range of 70-90℃, for example, 80℃ is selected; the curing time is controlled in the range of 1.5-3.0h, for example, 2h is selected. By precisely controlling these process parameter ranges, the leakage current response thin film material meeting the performance requirements can be more stably prepared.

[0078] The embodiment provides an application of the leakage current response thin film material in leakage current detection of power equipment, the leakage current response thin film material is made into a visual indicator device, which is used for directly attaching to the surface of the power equipment, and indicating the leakage state through color change driven by the leakage current.

[0079] In specific implementation, first, the electric leakage response thin film material prepared according to the method is cut and packaged (if necessary, a protective layer or adhesive is added) to form a visual indicator device that is easy to use. The device can be designed in the form of a patch, label or strip. Then, the visual indicator device is directly pasted or fixed on a key part or surface prone to electric leakage of a power equipment (such as a busbar of a high-voltage switch cabinet, an insulator or a cable terminal). When electric leakage occurs in the monitored power equipment, a weak electric leakage current will flow through (or an electric field effect will be generated near) the attached electric leakage response thin film material. The electrons in the electric leakage current will drive the tungsten trioxide particles in the thin film material to undergo a redox reaction with lithium ions, causing the tungsten trioxide to change from its intrinsic color (usually light yellow) to a dark color (usually blue). The operator can visually determine whether the equipment has electric leakage by observing whether the color of the indicator device changes. If the color changes significantly, it indicates that there is electric leakage, and further inspection and maintenance are required. Since the material has a memory effect, even if the electric leakage is intermittent, the color change can be maintained for a period of time, providing convenience for inspection. Specific embodiments

[0081] The present embodiment provides an electric leakage response thin film material, a preparation method, performance testing and practical application. The present embodiment provides an electric leakage response thin film material

[0082] The electric leakage response thin film material (hereinafter referred to as "detection patch") of the present embodiment has a single composite layer structure, and its specific components and characteristics are as follows:

[0083] Cross-linked polymer matrix:

[0084] Formed by epoxy-amine reaction of polyethylene glycol diglycidyl ether and polyether amine, the molar ratio of polyethylene glycol diglycidyl ether to polyether amine is controlled to be 1:0.8.

[0085] Tungsten trioxide particles:

[0086] In the final detection patch, the mass fraction of tungsten trioxide particles is 10wt%, the average particle size is 80nm, the specific surface area is 45m 2 / g, and the surface of the tungsten trioxide nanoparticles is modified by 3-aminopropyltriethoxysilane (APTES). The amine group density on the modified surface is determined to be 1.5 / nm 2 .

[0087] Lithium ion source:

[0088] Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) is selected as the lithium ion source. In the final detection patch, the mass fraction of LiTFSI is 25wt%.

[0089] Matrix material ratio: the balance (65% by mass) is a cross-linked polymer matrix formed by the reaction of the above polyethylene glycol diglycidyl ether and polyether amine.

[0090] Film thickness: the thickness of the final formed detection patch is controlled at 120 pm.

[0091] Matrix performance: the ion conductivity of the formed cross-linked polymer matrix (containing LiTFSI) is about 2.5 x 10 -4 S / cm, and the volume resistivity is about 5 x 10 14 Ω·cm.

[0092] Secondly, the embodiment provides a preparation method of an electric leakage responsive film material

[0093] The embodiment provides a preparation method of an electric leakage responsive film material, and specifically comprises the following steps:

[0094] Step S1: preparation of a prepolymer

[0095] According to the molar ratio 1:0.8, polyethylene glycol diglycidyl ether and polyether amine (with an average molecular weight of about 400 g / mol) are respectively weighed; the polyethylene glycol diglycidyl ether and the polyether amine are uniformly mixed in a clean glass beaker, and the mixture is placed in a constant temperature water bath at 60°C, and a prepolymerization reaction is carried out under magnetic stirring for 30 min to form a clear, low-viscosity prepolymer with appropriate viscosity.

[0096] Step S2: preparation of a uniform slurry

[0097] After the prepolymer is cooled to room temperature, APTES surface modified tungsten trioxide nanoparticles and LiTFSI powder are added thereto, and a glass rod is used for preliminary manual stirring and mixing, and then transferred to a high-speed shearing emulsifier, and sheared and dispersed at a speed of 5000 rpm for 30 min; then, the mixture is placed in an ultrasonic cell crusher, and ultrasonic dispersion is carried out at a power of 200 W for 30 min, so that the tungsten trioxide particles and LiTFSI are fully and uniformly dispersed in the prepolymer, and a uniform slurry without obvious particle agglomeration is obtained.

[0098] Step S3: film formation and curing

[0099] The prepared uniform slurry is uniformly coated on a pre-cleaned and treated PET flexible substrate by a slot coater (the gap of the doctor blade is set to obtain the target wet film thickness), and the PET substrate coated with the slurry is horizontally placed in a blast oven at 80°C for curing treatment for 2 h. In this process, the epoxy groups and amine groups undergo sufficient cross-linking reaction to form a stable three-dimensional network structure.

[0100] After curing is complete, remove the film from the oven and allow it to cool naturally to room temperature. Peel the resulting single composite film from the PET substrate (or retain the PET as a supporting protective layer) to obtain the target leakage-responsive film material. This can be cut into test patches of a specific size as needed, and double-sided tape can be applied to the back for easy installation.

[0101] 3. Performance Testing

[0102] 1. Analysis of element distribution on material surface

[0103] Methods: The prepared test patch samples were selected and their surfaces were observed using a scanning electron microscope (SEM). Furthermore, elemental surface analysis was performed using an accompanying energy dispersive X-ray spectrometer (EDS), focusing on the distribution of tungsten (W), sulfur (S), and fluorine (F).

[0104] Results: As Figure 1 、 Figure 2 and Figure 3 The EDS element distribution diagram shown (corresponding to F, S and W elements, respectively, Figure 1 is the distribution diagram of F element, Figure 2 is the distribution diagram of S element, Figure 3 This is the distribution diagram of the W element, the scale in the figure is 5μm), and it can be clearly observed:

[0105] Fluorine (F) element (represents TFSI in LiTFSI - Anions) also showed a uniform distribution of blue-green signal points in the observed microscopic area, which was highly consistent with the distribution trend of sulfur element, further confirming the uniform dispersion of LiTFSI.

[0106] Sulfur (S) element (represents TFSI in LiTFSI - Anions) showed a uniform orange-yellow signal point distribution in the observed microscopic area, covering the entire scanning area, indicating that LiTFSI was well dispersed in the matrix.

[0107] Tungsten (W) elements (representing tungsten trioxide particles) appear as small, diffuse red bright dots in the observed microscopic area, with uniform overall coverage and no obvious large-sized particle agglomeration.

[0108] These results intuitively demonstrate that tungsten trioxide particles and lithium ion source (LiTFSI) can be highly uniformly dispersed in the cross-linked polymer matrix formed by polyethylene glycol diglycidyl ether and polyetheramine, forming a single composite layer material with uniform structure. This uniform microstructure is the basis for achieving the material's excellent and stable macroscopic electrochromic performance, ion conductivity performance, and mechanical properties.

[0109] 2. Response threshold current, response time and color change path test

[0110] Method: The test patch was placed on the test platform, and different sizes of direct current were applied to both ends of the patch through an adjustable micro-current source. The CIE chromaticity coordinates (x, y) of the material surface under different power-on times (or different currents) were recorded using a color difference meter, and the minimum current value (threshold current) at which the color began to change visibly with the naked eye and the time required from power-on to the occurrence of a discernible color change (response time) were recorded simultaneously using the human eye.

[0111] Results:

[0112] The test results are shown in Figure 4 It can be seen from Figure 4 that the test patch prepared in this embodiment can observe the preliminary color change within 3 seconds when a direct current of 1 μA is applied. When the current increases to 2 μA, the color change becomes more obvious within 5 seconds.

[0113] Color change path (refer to CIE chromaticity diagram, as shown in Figure 5 ): In the initial unpowered state, the material presents a light yellow color, and its CIE chromaticity coordinates are about (x = 0.30, y = 0.36). After applying a current of 5 μA for 1 min, the material turns into a deep blue color, and its CIE chromaticity coordinates migrate to about (x = 0.18, y = 0.08). The entire color change process presents a clear path of migration from the yellow light region to the blue-violet light region on the CIE chromaticity diagram, indicating that the color change is significant and quantifiable.

[0114] 3. Color memory effect test

[0115] Method: Select a test patch, apply a direct current of 5 μA for 1 min, and fully develop the color to a deep blue color (corresponding to the CIE coordinates about (x = 0.18, y = 0.08) described above). Then remove the current and place the patch in a room temperature, light-free environment. Take pictures at regular intervals and record the chromaticity coordinates using a color difference meter, and observe continuously for more than 15 days.

[0116] Results: The test results are shown in Figure 6 It can be seen from Figure 6 that within 15 days after the current is removed, the deep blue state of the patch remains basically stable, and the color fading rate is less than 5% compared with the initial deep blue state. The naked eye can still clearly distinguish the color difference from the unpowered patch. This indicates that the material has excellent long-term memory effect.

[0117] 4. Breakdown field strength test:

[0118] Methods: Multiple groups (e.g., at least 10 samples) of test patches (120 μm thick) containing 1, 5, 10, 20, or 50 wt% tungsten trioxide were subjected to breakdown tests. The samples were sandwiched between two flat electrodes and the DC voltage applied between the electrodes was gradually increased while the current through the patch was monitored. When the current suddenly increased, the voltage and patch thickness at that moment were recorded, and the breakdown field strength was calculated. The data were statistically analyzed using a Weibull distribution.

[0119] Results: According to the statistical analysis of Weibull distribution (refer to Figure 7 ),Depend on Figure 7 It can be seen that for the detection patch containing 10wt% tungsten trioxide, its characteristic breakdown field strength (corresponding to a 63.2% breakdown probability) reaches about 15.16kV / mm, which shows that the material with this specific tungsten trioxide content has excellent high-voltage resistance.

[0120] 5. Flexibility and bending cycle durability test

[0121] To evaluate the mechanical stability and electrochromic performance retention of the detection patch under repeated bending deformation conditions, simulating its actual use when attached to a curved surface or subjected to vibration, the prepared detection patch was cut into strip samples measuring 1 cm × 5 cm.

[0122] Static bending test:

[0123] Method: Bend the sample 180° around a cylinder of varying diameters to see if it fits snugly without cracking. Minimum bending diameters can be 10mm, 5mm, or even 2mm.

[0124] Results: The test patch prepared in this example can be easily bent and tightly fit the surface of a cylinder with a diameter of 5 mm without breaking or visible cracks, showing good initial flexibility.

[0125] Dynamic bending cycle test:

[0126] Method: Select a sample and secure it to a dynamic bending tester (or manually simulate it). Set the bending parameters: bend radius 10mm, bend angle ±90° (i.e., one cycle consists of bending 90° in one direction, returning to the plane, then bending 90° in the opposite direction, and then returning to the plane), and bend rate 30 times / min. Perform 1000 bending cycles.

[0127] Evaluation indicators:

[0128] Appearance inspection: After the bending cycle test, use a magnifying glass or low-power microscope to observe whether there is mechanical damage such as cracks, delamination, wrinkles or breakage on the surface and edges of the sample.

[0129] Electrochromic performance test: Apply the same micro-current (e.g. 5 μA) to the sample after bending cycle as the un-bent sample, observe and record its response time, maximum color change and color memory effect. Compare it with the performance of the control sample without bending cycle.

[0130] Results:

[0131] Appearance: After 1000 bending cycles, no obvious cracks, delamination or breakage were observed on the surface of the patch sample, only a very slight wrinkle might be present at the edge of the extreme bending area, which did not affect the overall integrity.

[0132] Electrochromic performance: After bending cycle, the response time and color change depth of the sample after applying 5 μA current were less than 10% different from the un-bent control sample. Its color memory effect also remained basically unchanged. This indicates that repeated bending has little effect on the electrochromic core function of the material.

[0133] This fully proves that the leakage-responsive thin film material prepared in this embodiment has excellent flexibility and good mechanical durability, and can withstand the bending and deformation that may be encountered in actual application, maintaining its structural integrity and functional stability.

[0134] Four, the application of a leakage-responsive thin film material is provided

[0135] This embodiment provides visual monitoring of leakage current of key components in a high-voltage switch cabinet

[0136] Application scenario selection and preparation:

[0137] Target equipment: Select a 10kV indoor high-voltage switch cabinet in operation or planned for maintenance as the application object.

[0138] Monitoring point selection: According to the risk points prone to insulation deterioration or leakage in the high-voltage switch cabinet, the following typical positions are selected as the installation points of the detection patch:

[0139] The sub-surface of the insulation support of the main busbar of phase A, phase B and phase C: Especially the edge area where the support sub and the busbar contact.

[0140] The surface of the insulation partition of the static contact box of the circuit breaker trolley (or fixed circuit breaker).

[0141] The surface of the insulation sleeve of the high-voltage lead of the voltage transformer (PT) primary side.

[0142] The area near the cable outer sheath and stress cone at the connection between the cable terminal and the equipment.

[0143] The surface of the insulation part near the heater or humidity controller in the cabinet that may be affected by moisture.

[0144] Surface cleaning: Before installing the detection patch, use anhydrous ethanol or special insulating cleaner to thoroughly clean the surface of the selected installation point, remove dust, oil and moisture, and ensure that the patch can be well adhered.

[0145] Preparation and installation of detection patch:

[0146] Device: The leakage response film material prepared according to the present embodiment is cut into patches of different sizes and shapes, such as a 20mm x 50mm long strip for attaching to the surface of an insulator, and a 30mm diameter circle for attaching to certain flat areas. In order to facilitate installation and provide mechanical protection, a thin insulating protective film (such as transparent PET film) can be laminated on the non-sensing side of the patch, and industrial double-sided adhesive tape with good adhesion can be attached to the outside of the protective film.

[0147] Numbering and recording: Each detection patch is uniquely numbered, and the number, specific location of installation, installation date, etc. are recorded when installed, and a monitoring file is established.

[0148] Installation operation: Ensure that the switch cabinet is in a power-off maintenance state. Carefully tear off the release paper of the prepared detection patch, press it firmly to make it adhere to the surface of the pre-selected and cleaned monitoring point. Ensure that the patch is in close contact with the surface of the device without bubbles or edges.

[0149] Monitoring and inspection process:

[0150] Initial state recording: Before the switch cabinet is restored to power, take a photo of all installed detection patches and record their initial color state (which should be light yellow).

[0151] Routine inspection: During daily or periodic inspection (e.g. once a day or once a week), the color of the detection patch will be observed as part of the inspection.

[0152] Observation focus: Pay attention to whether the patch changes from the initial light yellow to blue or dark blue.

[0153] Contrast observation: Color comparison can be made with nearby reference patches of the same batch that have not experienced leakage (if reserved) or historical photos.

[0154] Abnormal situation handling:

[0155] Color change: If a patch is found to have a slight blue trend, the monitoring frequency of that location should be increased, and other methods such as infrared thermal imaging and partial discharge detection should be used for comprehensive judgment.

[0156] Color change significantly (dark blue): If a patch is found to be significantly dark blue, it is highly suspected that there is a persistent or cumulative effect of significant leakage current at this location. The situation should be immediately reported and a detailed inspection of the switchgear should be arranged to find out the cause of the leakage (such as dirt on the surface of the insulator, cracks, loose connections, etc.) and to handle it.

[0157] Color memory effect utilization: Due to the long-term memory effect of the patch, even if the leakage is intermittent, as long as the cumulative leakage charge reaches a certain level, the patch will change color and remain. Therefore, even if the leakage moment is not directly "captured" during the inspection, the colored patch can indicate that leakage has occurred at this location.

[0158] Data recording and analysis:

[0159] Maintenance personnel should record the color state of each detection patch regularly, which can be done by combining photos with written descriptions.

[0160] For patches that have changed color, the time of discovery, color depth, corresponding equipment working conditions (load, environmental temperature and humidity, etc.), and subsequent inspection and treatment measures should be recorded in detail.

[0161] Long-term accumulated data can be used to analyze the leakage trend of specific equipment or specific locations, providing a basis for preventive maintenance.

[0162] Maintenance and replacement:

[0163] Life assessment: Based on the stability of the material and the actual application environment, assess the effective service life of the detection patch (for example, based on accelerated aging test results or manufacturer's recommendations).

[0164] Regular replacement: It is recommended to replace all detection patches uniformly when the equipment is overhauled or reaches the estimated life, to ensure the reliability of monitoring.

[0165] Damage replacement: If the patch is found to have physical damage (such as scratches, falling off) or performance degradation due to extreme environment, it should be replaced in time.

[0166] Evaluation of application effect:

[0167] In this embodiment, by installing such a single composite layer structure of leakage response detection patch in multiple key positions in the high-voltage switch cabinet, early and visual warning of potential leakage current is successfully achieved. For example, when a certain insulator surface produces a few microamperes (μA) of leakage current due to dirt accumulation and moisture, the detection patch installed on its surface can change from the initial light yellow (CIEx≈0.30, y≈0.36) to a recognizable blue color within a few seconds to a few minutes. Even if the leakage phenomenon disappears in a short time, due to the excellent color memory effect of the material (fading rate <5% for more than 15 days), the colored patch can still provide clear fault indication for subsequent inspection personnel. The material's characteristic breakdown field strength of up to about 15.16 kV / mm ensures its safe application under a 10 kV working voltage, and the good flexibility allows it to be easily adapted to various complex installation surfaces. Through this intuitive, low-cost, and maintenance-free (or low-maintenance) monitoring method, the ability of operation and maintenance personnel to discover early insulation defects is greatly improved, effectively preventing equipment failures and safety accidents caused by leakage, and providing an innovative technical means for the safe and stable operation of the power system.

[0168] The above merely illustrates the specific embodiments of the present application, but the protection scope of the present application is not limited thereto, and any person skilled in the art can easily think of changes or replacements within the technical range disclosed by the present application, which shall be covered within the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the protection scope of the claims.

Claims

1. A leakage current responsive thin film material, characterized in that: The leakage current responsive thin film material is a single composite layer, which includes: a cross-linked polymer matrix formed by the epoxy-amine reaction of polyethylene glycol diglycidyl ether and polyetheramine; Tungsten trioxide particles dispersed in the cross-linked polymer matrix; and A source of lithium ions is dispersed in the cross-linked polymer matrix.

2. The leakage current responsive thin film material according to claim 1, characterized in that: The molar ratio of the polyethylene glycol diglycidyl ether to the polyetheramine is 1:(0.7-0.9).

3. The leakage current responsive thin film material according to claim 1, characterized in that: The leakage current responsive thin film material comprises: The tungsten trioxide particles account for 1%-50% by mass; 1% to 25% by mass of the lithium ion source; and The balance is the cross-linked polymer matrix.

4. The leakage current responsive thin film material according to claim 1, characterized in that: The particle size of the tungsten trioxide particles is 50nm-200nm, and the specific surface area is ≥30m 2 / g, the surface of the tungsten trioxide particles is modified with 3-aminopropyltriethoxysilane, and the surface amine density after modification is ≥1.2 / nm 2 .

5. The leakage current responsive thin film material according to claim 1, characterized in that: The lithium ion source is at least one selected from lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate and lithium bis(fluorosulfonyl)imide.

6. The leakage current responsive thin film material according to claim 1, characterized in that: The thickness of the leakage current response thin film material is 50 μm-200 μm.

7. The leakage current responsive thin film material according to any one of claims 1 to 6, characterized in that: The ionic conductivity of the cross-linked polymer matrix is ​​greater than 1×10 -4 S / cm, and the volume resistivity of the cross-linked polymer matrix is ​​greater than 1×10 14 Ω·cm.

8. A method for preparing the leakage current responsive thin film material according to claim 7, characterized in that: The following steps are involved: S1, mixing polyethylene glycol diglycidyl ether and polyetheramine and performing a prepolymerization reaction to form a low-viscosity prepolymer; S2, adding tungsten trioxide particles and a lithium ion source to the low-viscosity prepolymer, and performing a dispersion treatment to obtain a uniform slurry; S3, forming a film of the uniform slurry on a substrate, and performing a curing treatment to form the cross-linked polymer matrix, thereby obtaining the leakage current responsive thin film material.

9. The method according to claim 8, characterized in that The prepolymerization reaction conditions in step S1 are 20 min-45 min at 50°C-70°C; the dispersion treatment in step S2 includes high-speed shear emulsification and ultrasonic dispersion, and the dispersion time is 0.5h-1.5h; the film formation in step S3 adopts a slit coating method, and the curing treatment conditions are 1.5h-3.0h at 70°C-90°C.

10. An application of the leakage current responsive thin film material according to claim 7 in leakage current detection of power equipment, characterized in that: The leakage responsive thin film material is made into a visual indicator device, which is used to be directly attached to the surface of an electric device and indicates the leakage state through the color change driven by the leakage current.